Kinetic and thermodynamic studies of the interaction between activating and inhibitory Ly49 natural killer receptors and MHC class I molecules - Romasanta, Pablo Nicolas (2016)
Natural killer (NK) cells are lymphocytes of the innate immune system that eliminate virally infected or malignantly transformed cells. NK cell function is regulated by diverse surface receptors that are both activating and inhibitory. Among them, the homodimeric Ly49 receptors control NK cell cytotoxicity by sensing major histocompatibility complex class I molecules (MHC-I) on target cells. Although crystal structures have been reported for Ly49/MHC-I complexes, the underlying binding mechanism has not been elucidated. Accordingly, we carried out thermodynamic and kinetic experiments on the interaction of four NK Ly49 receptors (Ly49G, Ly49H, Ly49I and Ly49P) with two MHC-I ligands (H-2Dd and H-2Dk). These Ly49s embrace the structural and functional diversity of the highly polymorphic Ly49 family. Combining surface plasmon resonance, fluorescence anisotropy and far-UV circular dichroism (CD), we determined that the best model to describe both inhibitory and activating Ly49/MHC-I interactions is one in which the two MHC-I binding sites of the Ly49 homodimer present similar binding constants for the two sites (∼106 M–1) with a slightly positive co-operativity in some cases, and without far-UV CD observable conformational changes. Furthermore, Ly49/MHC-I interactions are diffusion-controlled and enthalpy-driven. These features stand in marked contrast with the activation-controlled and entropy-driven interaction of Ly49s with the viral immunoevasin m157, which is characterized by strong positive co-operativity and conformational selection. These differences are explained by the distinct structures of Ly49/MHC-I and Ly49/m157 complexes. Moreover, they reflect the opposing roles of NK cells to rapidly scan for virally infected cells and of viruses to escape detection using immunoevasins such as m157.